2016
DOI: 10.1590/1676-0611-bn-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal distribution of the ichthyofauna in a tributary of Tietê River with sources on the Basaltic Cuestas of São Paulo, Southeastern Brazil

Abstract: This work aimed to study the composition and distribution of fish species at four sites along Cabeça River, an affluent of Corumbataí River, tributary of Tietê River, intending to better understand the influence of local geomorphology on the occurrence of the species along the river. Using gill nets, trawl net, cast net and sieves, five samples were taken from each site every two months. These data were analyzed from constancy of occurrence, similarity index of Jaccard, rarefaction analysis and descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Langeani et al (2007) showed that Characidae and Loricariidae, in general, are the two most species-rich families of the upper Rio Paraná basin. In addition, several ichthyofaunal surveys (e.g., , Smith et al 2007, Oliveira et al 2009, Fagundes et al 2015, Hoffmann et al 2015, Cardoso et al 2016, Frota et al 2016 show this pattern in tributaries of the basin. However, in our work Cichlidae was the second most represented family (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Langeani et al (2007) showed that Characidae and Loricariidae, in general, are the two most species-rich families of the upper Rio Paraná basin. In addition, several ichthyofaunal surveys (e.g., , Smith et al 2007, Oliveira et al 2009, Fagundes et al 2015, Hoffmann et al 2015, Cardoso et al 2016, Frota et al 2016 show this pattern in tributaries of the basin. However, in our work Cichlidae was the second most represented family (Fig.…”
Section: Discussionmentioning
confidence: 86%